APLIKASI PUPUK ORGANIK CAIR DAN BIOPESTISIDA PADA PERTANIAN PADI ORGANIK DI SUBAK REJASA KECAMATAN PENEBEL KABUPATEN TABANAN - N.N. Soniari; N.M. Witariadi; N.K. Karyati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
One of the goals of science and technology for the Region of Jegu and RejasaVilages in Penebel District,Tabanan Regency is a healthy increase rice productivity by application of liquid organic fertilizer andartificial biopesticides farmers themselves. The method adopted to achieve these goals is through education,training, simulation science and technology, mentoring, and design appropriate technology applied.All suchactivities are realized in the form of a field school that was attended by 25 members of SubakRejasa bymaking healthy rice demonstration plot 25 acres.POC and biopesticide made from animal waste, sugar cane,Gamal, yam tubers and other local materials, applied at a dose of 450 ml / 25 L of water every week. Liquidorganic fertilizer and biopesticide made by members of SubakRejasa have done laboratory analysis with thefollowing results: the content of C-org (1,540%): N (0.160%); P (85.120 ppm); K (95.400 ppm); pH (7.78)and DHL (32,200 mS). The results of the application of POC and biopesticideson the rice varieties